Towards greater private sector uptake on urban greenery in Melbourne - Ong, Boon Lay; Hes, Dominique; Aye, L.; Fryd, Ole; Tuan, Duc-Ngo
The City of Melbourne unveiled its Urban Forest Strategy in late 2013, setting out plans to rejuvenate and intensify the city’s urban greenery. As identified in the strategy, the community, both as public and private businesses, is expected to be an integral participant in the strategy. Recently, the University of Melbourne was engaged by the City to collaborate in a study to investigate the perception and expectations of the private sector in terms of the uptake of urban greenery. The study involved two workshops where prepared presentations were used to initiate discussions and feedback. The key finding is that most research findings do not directly address business priorities. Analysis of the feedback indicated three areas for further investigation: the need to develop business cases pertinent to individual businesses, the need for a greenery standard, and the need to develop public-private partnerships in implementing urban greenery. We present our initial thoughts on these three areas and suggest some directions for future research.